Youth unemployment in the European Union and transition period - from education to the labour market - Pkhakadze, Tamar (Technium Social Sciences Journal, 2022)
The difference between youth and adult unemployment can be based on the high-level job mobility caused by the globalisation process, as well as the higher possibility of passiveness among the younger generation. The inactivity rate is quite diverse in different countries and is directly linked to youth unemployment. To compare adult and youth inactivity in the European Union, youth perform at a four times higher rate than the adult population. Higher inactivity usually has a direct link to entering into formal education. The transition process in this chapter describes the period from educational institutions to a stable working position. The transition period generally reflects the processes itself and how young people enter the labour market, along with how entry to the labour market is regulated and what the general consequences are for young job-seekers during this time. During the transition period, individual resources and the background of the person play an essential role while also coming with some consequences and barriers.